The Influence of Technological Readiness, Instructional Leadership and Workload Management on Teacher Performance: Penelitian - Riyanti, Apriani; Osman, Isnawati; Rais, Rinovian; Warsono; Haddar, Gamar Al; Rif'an, Muhamad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The main goal of the study is to analyze how technology readiness, instructional leadership, and workload management together influence teacher performance. The researchers have pointed out the necessity of teaching professionals in the digital era to be not only trained but also paid well, which will be the case when the teachers take the lead in the learning process. The study was designed as a quantitative explanatory research method involving the participation of 150 teachers who were chosen intentionally. Data collection was done through a five-point Likert scale questionnaire while multiple linear regression analysis was the statistical method used. The research tool was initially subjected to validation, reliability testing with Cronbach's Alpha, and classical assumptions before analysis. The findings indicated that each of the three independent variables significantly and positively affected teacher performance. Theoretical implications of the research have reached the area of educational management and human resources in education. The practical implications of the research, on the other hand, indicate that there are school strategies to enhance teacher performance in terms of technology, instructional leaders, and managing workload.